Slowness and Renewed Perception: Revisiting Douglas Gordon’s 24 Hour Psycho (1993) with Don DeLillo’s Point Omega (2010) - Françoise Sammarcelli (Sillages Critiques)
In 1993 Douglas Gordon appropriated Alfred Hitchcock’s famous film Psycho and slowed it down to approximately two frames a second (instead of the usual twenty-four). The resulting work, 24 Hour Psycho, is a silent, disorienting installation that draws our attention to time and memory while questioning authorship. This article analyzes how American writer Don DeLillo revisits Gordon’s installation in his novel Point Omega (2010), which allows him to experiment with the relations between contemporary art and fiction. After presenting these various works and the intersemiotic reflexion they activate in DeLillo’s novel, the essay examines the deceptive simplicity of this brief text, in terms of syntax and diegetic structure (including the film-related framing device). Using Henri Bergson’s difference between chronological time and duration, it also focuses on DeLillo’s exploration of time (acceleration and deceleration, action and contemplation). It then argues that Point Omega can be read as a complex theoretical essay, blurring the boundaries between genres, notably by establishing a dialogue with Gordon and Jesuit philosopher Teilhard de Chardin, while problematizing academic discourse. Lastly, relying on Deleuze’s texts on cinema (and on Hitchcock in particular), and on phenomenological thinking, the essay focuses on the position of the reader/viewer, between implication and distance, perception and performance.